A framework to analyze project management cognitive process using MNE-Python - Sulbaran, Tulio; Kisi, Krishna (American Journal of STEM Education, 2024)
The objective of this paper is to present a comprehensive and simple framework utilizing MNE-Python to investigate the cognitive processes involved in project management tasks. MNE-Python was selected because it is a powerful Python library for analyzing brain activity data from magnetoencephalography (MEG) and electroencephalography (EEG) experiments. The methodology used was qualitative conceptual research to build conceptual frameworks for phenomena linked to multidisciplinary bodies of knowledge. The resulting framework is organized in several key stages: import data fNIRS Raw Data, preprocess data and visualization, analysis and statistical testing, and interpret findings.  The implication of this work includes bridging the gap between neuroscience and project management research by providing a framework for studying the cognitive processes underlying project management tasks, the proposed framework holds promise for advancing our understanding of how project managers navigate complex environments, make strategic decisions, and optimize project outcomes.